Determinant Percieved Usefulness in Decision Making on Accrual Based Accounting in Indonesian Ministries - Metalia, Mega (E-Jurnal Akuntansi; Vol 32 No 9 (2022)DO - 10.24843/EJA.2022.v32.i09.p17, 2022)
This study intends to investigate the impact of managerial ability, internal control effectiveness, and support from information technology on the quality of accrual accounting implementation and its effects on perceptions of utility in decision-making. In 87 ministries and institutions of the Republic of Indonesia, this research approach uses a survey that combines descriptive and verification analysis with units of analysis. The sort of data used comprises secondary and primary data, and it was tested using SEM and LISREL analysis strategy. The findings demonstrated that: information technology support, managerial competence, and the effectiveness of internal control have a positive effect on the quality of accrual accounting implementation; the quality of accrual accounting implementation has a positive impact on perceptions of usefulness in decision making; and information technology support, managerial competence, and the effectiveness of internal control have a positive impact on perceptions of the usefulness of accrual accounting application. Keyword: Information Technology Support; Managerial Competence; Effectiveness of Internal Control; Quality of Accrual Accounting Application; Perceived Usefulness in Decision Making